Single-dose tinidazole for the treatment of giardiasis. - Speelman, P (1985)
Sixty-three expatriate residents and travellers in Bangladesh, infected with Giardia lamblia, participated in two studies to compare the therapeutic efficacy of tinidazole and metronidazole. In the first trial 33 randomly selected patients were treated with tinidazole (50 mg/kg of body weight to a maximum of 2 g) or metronidazole (60 mg/kg of body weight to a maximum of 2.4 g) in a single oral dose. Patients were followed for 4 weeks after the end of therapy for the presence of G. lamblia in their stools. Sixteen (94%) of 17 patients receiving tinidazole were free of G. lamblia during that period, compared to only 9 (56%) of 16 patients who had received metronidazole (P less than 0.02). In the second trial patients were randomly allocated to a treatment schedule of either metronidazole as a single dose on 3 successive days (50 mg/kg of body weight to a maximum of 2 g daily) or tinidazole as a single oral dose (50 mg/kg of body weight to a maximum of 2 g). All 15 patients treated with tinidazole and 14 (93%) of 15 patients treated with metronidazole were free of G. lamblia during the 4-week follow-up period. A single oral dose of tinidazole is a highly effective treatment for giardiasis and is equal in efficacy to a 3-day therapy with metronidazole.